Semiquantitative Scale for Assessing Brain MRI Abnormalities in Wilson Disease: A Validation Study - Dusek, Petr; Smolinski, Lukasz; Redzia-Ogrodnik, Barbara; Golebiowski, Marek; Skowronska, Marta; Poujois, Aurelia; Laurencin, Chloe; Jastrzebska-Kurkowska, Iwona; Litwin, Tomasz; Członkowska, Anna (Movement disorders, 2020)
BACKGROUND: MRI is a sensitive method for the assessment of brain abnormalities in Wilson disease, that is, T2 hyperintensities, T2 hypointensities, and atrophy, but a validated scoring system for the classification of radiological severity is lacking. The objective of this study was to develop and validate a brain MRI visual rating scale for Wilson disease. METHODS: The proposed Wilson disease brain MRI severity scale consists of acute toxicity and chronic damage subscores from predefined structures. The former, calculated by summing scores of T2 hyperintensities (excluding cavitation), is likely to be partially reversible with treatment. The latter, representing the sum of scores of T2 hypointensities and brain atrophy, reflects pathology that is not readily reversible. Validation was performed on MRI scans acquired using 1.5T system from 39 Wilson disease patients examined at baseline and after 24 months on anticopper treatment. Intraclass correlation coefficients of 5 ratings from 3 raters were calculated. Temporal evolution of the MRI severity score and its association with clinical severity, assessed using the Unified Wilson Disease Rating Scale part III, was calculated. RESULTS: Intrarater and interrater agreement were good (r > 0.93; P < 0.001; and r > 0.74; P < 0.001, respectively). In neurologic Wilson disease patients, the total MRI severity score improved over 2 years (P = 0.032), mainly because of reduced acute toxicity (P = 0.0015), whereas the chronic damage score deteriorated (P = 0.035). Unified Wilson Disease Rating Scale part III score was positively associated with chronic damage and total score at baseline (P = 0.005 and P = 0.003, respectively) and in month 24 (P < 0.001 and P = 0.001, respectively). CONCLUSIONS: The Wilson disease brain MRI severity scale is a simple, reliable, and valid instrument that allows semiquantitative assessment of radiological Wilson disease severity. © 2020 International Parkinson and Movement Disorder Society.
Keywords: Brain Diseases; Reproducibility of Results; clinical scales; mozek; MRI; neuroradiology; Wilson disease; Humans; Magnetic Resonance Imaging; lidé; hepatolentikulární degenerace; nemoci mozku; magnetická rezonanční tomografie; reprodukovatelnost výsledků; Hepatolenticular Degeneration; Brain